Association of random glucose to albumin ratio with post-contrast acute kidney injury and clinical outcomes in patients with ST-elevation myocardial infarction - Lai, Ping; Gu, Xiaoyan; Lin, Xuhui; He, Yu; Dai, Yining; Duan, Chongyang; Liu, Yuanhui; He, Wenfei (Frontiers in Endocrinology, 2024)
Purpose Both glucose and albumin are associated with chronic inflammation, which plays a vital role in post-contrast acute kidney injury (PC-AKI). To explore the relationship between random glucose to albumin ratio (RAR) and the incidence of PC-AKI after percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI). Patients and methods STEMI patients who underwent PCI were consecutively enrolled from January, 01, 2010 to February, 28, 2020. All patients were categorized into T1, T2, and T3 groups, respectively, based on RAR value (RAR < 3.377; 3.377 ≤ RAR ≤ 4.579; RAR > 4.579). The primary outcome was the incidence of PC-AKI, and the incidence of major adverse clinical events (MACE) was the second endpoint. The association between RAR and PC-AKI was assessed by multivariable logistic regression analysis. Results A total of 2,924 patients with STEMI undergoing PCI were finally included. The incidence of PC-AKI increased with the increasing tertile of RAR (3.2% vs 4.8% vs 10.6%, P<0.001). Multivariable regression analysis demonstrated that RAR (as a continuous variable) was associated with the incidence of PC-AKI (adjusted odds ratio (OR) =1.10, 95% confidence interval (CI) =1.04 - 1.16, P<0.001) and in-hospital MACE (OR=1.07, 95% CI=1.02 - 1.14, P=0.012); RAR, as a categorical variable, was significantly associated with PC-AKI (T3 vs. T1, OR=1.70, 95% CI=1.08 - 2.67, P=0.021) and in-hospital MACE (T3 vs. T1, OR=1.63, 95% CI=1.02 - 2.60, P=0.041) in multivariable regression analyses. Receiver operating characteristic curve analysis showed that RAR exhibited a predictive value for PC-AKI (area under the curve (AUC)=0.666, 95% CI=0.625 - 0.708), and in-hospital MACE (AUC= 0.662, 95% CI =0.619 - 0.706). Conclusions The high value of RAR was significantly associated with the increasing risk of PC-AKI and in-hospital MACE after PCI in STEMI patients, and RAR offers a good predictive value for those outcomes.